Large shareholders and accounting research - Ole-Kristian Hope (China Journal of Accounting Research, 2013)
Large shareholders are a potentially very important element of firms' corporate governance system. Whereas analytical research is typically vague on who these large shareholders are, in practice there are important variations in the types of large owners (and the different types of large owners could play very different governance roles). After briefly reviewing the standard agency cost arguments, in this article I emphasize the heterogeneity of concentrated ownership and in particular focus on the roles of families, institutions, governments, and employee ownership. I also discuss the role of large shareholders in private (i.e., unlisted) firms, where ownership tends to be more concentrated than in publicly traded firms. Finally, I briefly discuss variations in ownership structures across selected countries.
Keywords: G30; G32; G38; M20; M41; 650; Large shareholders; Agency costs; Controlling owners; Minority owners; Private firms; International